The Development of Semiotic Based Contextual Mathematics Learning Videos to Support Learning from Home - Mu'jizatin Fadiana; Yulaikah Yulaikah; Diah Kusumawati (AL-ISHLAH: Jurnal Pendidikan, 2021)
This study aims to develop a contextual mathematics learning video based on semiotics that supports learning from home. This type of research is development research using a 4-D model, which is modified into three stages, namely define, design, and develop. The research subjects were grade 6th elementary school students in Tuban, East Java. In the defined stage, a needs analysis is carried out as a reference for development. The design stage produces research instruments and instructional video designs. The development stage states that based on the results of the validation of media experts by 85% and material experts by 87%, each of which comes from 21 points of assessment indicators, it shows that it meets the valid criteria as well as positive responses of 85.3% of 28 students. The right-hand t-test obtained t-count t-table, namely 3.886 1.675. It indicates that the learning outcomes of students who use semiotic-based contextual mathematics learning videos on the perimeter of circle material are better than students who do not use them. This learning video has reached effective criteria.